Finite element simulation of sherardising concentration field. (3rd May 2020) - Long, J.; Li, X.; Zhong, Y.; Zhang, Y.
ABSTRACT: Sherardising is a surface protection method for obtaining an Fe-Zn coating on a steel surface by thermal diffusion. This paper proposes a model to study the sherardising diffusion process of low carbon steel. The diffusion mathematical model of the zinc coating element is established by the finite element method, which simulates the changes of zinc concentration field with temperature and time in the sherardising process. In the experimental work the sherardised samples were prepared for 2, 6 and 10 h at 375°C and 2, 6 and 8 h at 405°C and 420°C. Each phase's thickness and the zinc concentration of the sherardising layer were measured by scanning electron microscopy and energy dispersive spectrometry respectively. The results show that the accuracy of the finite element method is verified by the consistency between the simulation results and the experimental results. This model can effectively guide the sherardising process to achieve optimum results.